RELEVANSI SIKAP BERAKUNTANSI PELAKU UMKM MUDA DAN PENGGUNAAN INFORMASI AKUNTANSI TERHADAP KEBERHASILAN USAHA - Ayu Dwidyah Rini; Kazia Laturette (Jurnal Riset Akuntansi dan Keuangan, 2016)
The effect of accounting attitude young SMEs and the use of accounting information to businesssuccess. This study aims to determine the relationship accounting attitude and use of accountinginformation businesses small and medium micro young to business success . Data was collectedthrough questionnaires with 100 young SMEs in Surabaya . The study uses a quantitative approachwith multiple linear regression analysis and snowball sampling to sampling . The results of the studyexplained that the accounting attitude young SMEs , accounting information has a significantrelationship in partial to business success. The results also explain that the accounting informationhas a dominant influence on the success of young SME business in Surabaya .Keywords: Accounting Information , Attitude, Business Success